2019
DOI: 10.1249/mss.0000000000001848
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Brain White Matter Microstructure of People with Lateral Ankle Sprain

Abstract: Purpose This study aimed to quantify differences in white matter microstructure and static postural control in individuals with and without a previous history of a lateral ankle sprain. Methods Ten participants with a history of a lateral ankle sprain and 10 controls performed three 20-s trials of single-leg static balance on a force platform under an eyes-open condition. Resultant sample entropy (SampEn) was used to assess static postural control perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 66 publications
1
30
2
Order By: Relevance
“…Collectively, these TMS studies suggest that supra-spinal adaptions may very well occur in patients with CAI and probably contribute to their sensorimotor impairments [33,34,35,36]. Supporting this, a recent magnetic resonance imaging study [89] assessed the white matter microstructure of the superior cerebellar peduncle by means of diffusion tensor imaging in patients with CAI and found lower white matter microstructure in CAI patients. At the same time, the CAI patients demonstrated worse postural control than healthy subjects.…”
Section: Discussionmentioning
confidence: 89%
“…Collectively, these TMS studies suggest that supra-spinal adaptions may very well occur in patients with CAI and probably contribute to their sensorimotor impairments [33,34,35,36]. Supporting this, a recent magnetic resonance imaging study [89] assessed the white matter microstructure of the superior cerebellar peduncle by means of diffusion tensor imaging in patients with CAI and found lower white matter microstructure in CAI patients. At the same time, the CAI patients demonstrated worse postural control than healthy subjects.…”
Section: Discussionmentioning
confidence: 89%
“…138 Research has also found impaired central mediated processes, including spinal-level sensorimotor control/reflex inhibition 36,64,121,145,171,226,227,292,308,338,403,406,407,423,433 and supraspinal corticomotor abnormalities. 171,308,330,332,375,377,424,426,428,458 These impaired sensorimotor and central mediated processes may be evident in both the injured and uninjured limbs and impact the movement system, as seen with static and dynamic balance, walking, stepping, running, jumping, cutting, and kicking. 88,105,108,264,396,403-407…”
Section: Pathoanatomical Features Update 2021mentioning
confidence: 99%
“…White matter microstructure, or anatomical connectivity, contributes to FC and is related to static postural control. 44,45 Finally, we recognize our relatively healthy sample prevents us from generalizing ndings to all older adults with history of LAS.…”
Section: Discussionmentioning
confidence: 94%
“…A trial was discarded if: 1) the non-testing limb made contact on the force platform or the stance limb; 2) participants hopped or took a step with the stance limb; 3) participant lifted their forefoot or heel from the force plate; and/or 4) they removed their hands from their hips. 44…”
Section: Resting-state Processingmentioning
confidence: 99%
See 1 more Smart Citation